Role of Receptor for Hyaluronic Acid-mediated Motility (RHAMM) in Low Molecular Weight Hyaluronan (LMWHA)-mediated Fibrosarcoma Cell Adhesion - Kouvidi, Katerina (American Society for Biochemistry and Molecular Biology, 2011)
Hyaluronan (HA) modulates key cancer cell functions through interaction with its CD44 and receptor for hyaluronic acid-mediated motility (RHAMM) receptors. HA was recently found to regulate the migration of fibrosarcoma cells in a manner specifically dependent on its size. Here, we investigated the effect of HA/RHAMM signaling on the ability of HT1080 fibrosarcoma cells to adhere onto fibronectin. Low molecular weight HA (LMWHA) significantly increased (p ≤ 0.01) the adhesion capacity of HT1080 cells, which high molecular weight HA inhibited. The ability of HT1080 RHAMM-deficient cells, but not of CD44-deficient ones, to adhere was significantly decreased (p ≤ 0.001) as compared with control cells. Importantly, the effect of LMWHA on HT1080 cell adhesion was completely attenuated in RHAMM-deficient cells. In contrast, adhesion of RHAMM-deficient cells was not sensitive to high molecular weight HA treatment, which identifies RHAMM as a specific conduit of the LMWHA effect. Western blot and real time-PCR analyses indicated that LMWHA significantly increased RHAMM transcript (p ≤ 0.05) and protein isoform levels (53%, 95 kDa; 37%, 73 kDa) in fibrosarcoma cells. Moreover, Western blot analyses showed that LMWHA in a RHAMM-dependent manner enhanced basal and adhesion-dependent ERK1/2 and focal adhesion kinase (FAK) phosphorylation in HT1080 cells. Utilization of a specific ERK1/2 inhibitor completely inhibited (p ≤ 0.001) LMWHA-dependent adhesion, suggesting that ERK1/2 is a downstream effector of LMWHA/RHAMM signaling. Likewise, the utilization of the specific ERK1 inhibitor resulted in a strong down-regulation of FAK activation in HT1080 cells, which identifies ERK1/2 as a FAK upstream activator. In conclusion, our results suggest that RHAMM/HA interaction regulates fibrosarcoma cell adhesion via the activation of FAK and ERK1/2 signaling pathways.